Utility of novel 2-furanones in synthesis of other heterocyclic compounds having anti-inflammatory activity with dual COX2/LOX inhibition - Rania H. Abd El-Hameed; Shahenda Mahgoub; Hend M. El-Shanbaky; Mosaad S. Mohamed; Sahar A. Ali (Taylor & Francis Group, 2021)
Inflammation is associated with the development of several diseases comprising cancer and cardiovascular disease. Agents that suppress cyclooxygenase (COX) and lipoxygenase (LOX) enzymes, besides chemokines have been suggested to minimise inflammation. Here, a variety of novel heterocyclic and non-heterocyclic compounds were prepared from novel three furanone derivatives. The structures of all synthesised compounds were confirmed by elemental and spectral analysis including mass, IR, and 1H-NMR spectroscopy. Anti-inflammatory activities of these synthesised compounds were examined in vitro against COX enzymes, 15-LOX, and tumour necrosis factor-α (TNF-α), using inhibition screening assays. The majority of these derivatives showed significant to high activities, with three pyridazinone derivatives (5b, 8b, and 8c) being the most promising anti-inflammatory agents with dual COX-2/15-LOX inhibition activities along with high TNF-α inhibition activity.